2016
DOI: 10.1016/j.matbio.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin microfibrils in bone physiology

Abstract: The severe skeletal abnormalities associated with Marfan syndrome (MFS) and congenital contractural arachnodactyly (CCA) underscore the notion that fibrillin assemblies (microfibrils and elastic fibers) play a critical role in bone formation and function in spite of representing a low abundance component of skeletal matrices. Studies of MFS and CCA mice have correlated the skeletal phenotypes of these mutant animals with distinct pathophysiological mechanisms that reflect the contextual contribution of fibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…We favor the latter possibility based on recent evidence indicating that the initial consequence of fibrillin-1 deficiency in the aorta of MFS mice is to impair rather than stimulate TGFβ activity [24]. In this respect, differential modulation of TGFβ activity in HSC and erythroid niches is in line with prior evidence that fibrillin microfibrils provide contextual specificity to TGFβ and BMP signals during bone patterning and remodeling [17]. We further argue that osteopenia-dependent expansion of hematopoietic tissue, as evidenced by increased marrow cellularity in fibrillin-1-deficient bones, may also contribute to HSC depletion independently of TGFβ dysregulation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We favor the latter possibility based on recent evidence indicating that the initial consequence of fibrillin-1 deficiency in the aorta of MFS mice is to impair rather than stimulate TGFβ activity [24]. In this respect, differential modulation of TGFβ activity in HSC and erythroid niches is in line with prior evidence that fibrillin microfibrils provide contextual specificity to TGFβ and BMP signals during bone patterning and remodeling [17]. We further argue that osteopenia-dependent expansion of hematopoietic tissue, as evidenced by increased marrow cellularity in fibrillin-1-deficient bones, may also contribute to HSC depletion independently of TGFβ dysregulation.…”
Section: Discussionsupporting
confidence: 56%
“…A case in point is the skeleton where fibrillin-1 and the structurally related fibrillin-2 protein have been shown to differentially modulate TGFβ and BMP signals during bone patterning and remodeling [17]. We have recently reported that fibrillin-1 influences MSC fate determination by controlling TGFβ bioavailability within adult marrow niches [18].…”
Section: Introductionmentioning
confidence: 99%
“…Murine models of MFS have focussed more on fibrillin-1 mutation-induced TGF-b perturbations than on structural microfibril defects as disease 'drivers' (Sengle & Sakai 2015;Smaldone & Ramirez 2016). The hypomorphic mgD mouse had pathologically elevated TGF-b activity in the lung (Neptune et al 2003), which correlated with initial predictions that perturbations in large latent TGF-b complexes interacting directly with fibrillin-1 (see LTBPs) would manifest as enhanced TGF-b signalling in affected tissues.…”
Section: 'Tall' Fibrillinopathiesmentioning
confidence: 85%
“…Murine models of MFS have focussed more on fibrillin‐1 mutation‐induced TGF‐β perturbations than on structural microfibril defects as disease ‘drivers’ (Sengle & Sakai ; Smaldone & Ramirez ). The hypomorphic mgΔ mouse had pathologically elevated TGF‐β activity in the lung (Neptune et al .…”
Section: ‘Tall’ Fibrillinopathiesmentioning
confidence: 99%
“…Furthermore, we were able to detect elevated TGFβ signaling in Mfap2 -/- adipose tissue but not in any of the fibrillin-1 mutant mice. MFS-associated skeletal anomalies have been documented in mouse models of fibrillin-1 disruption [24]. Despite lacking a metabolic phenotype, all three fibrillin-1 mutant lines recapitulated the Marfanoid features of long bone overgrowth and reduced bone mass.…”
Section: Introductionmentioning
confidence: 99%